MELACAK PEMIKIRAN KRITIS MUHAMMAD HAMIDULLAH: ANTARA ORIENTALISME DAN PENAFSIR QUR'AN-HADIS - Nurhaidah, Siti Nuri; Rahman; Hakam, Muhammad Haris; Karim, Abdul; Suhaimi (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This article examines Muhammad Hamidullah’s critical approach to the Quran and hadith, highlighting his significant contributions to Islamic scholarship. This literature-based study utilizes primary sources authored by Hamidullah, such as “Muhammad: The Prophet of Islam,” “A History of Muslim Philosophy,” “The Quran: A Critical Translation,” and “The Prophet’s Last Sermon,” complemented by secondary sources that contextualize his thoughts. Employing a juridical sociological approach, the research analyzes Hamidullah’s method of integrating critical and analytical perspectives within an Islamic framework. The findings reveal that Hamidullah’s work successfully bridges the intellectual gap between Western and Muslim scholarship through his application of critical historical methods. His contributions underscore the potential for a nuanced understanding of Islamic texts that respects both scholarly rigor and religious identity